2022
DOI: 10.33448/rsd-v11i1.24614
|View full text |Cite
|
Sign up to set email alerts
|

Análise epidemiológica de hanseníase no Brasil no período de 2016 a 2020

Abstract: Introdução: A hanseníase é uma doença crônica infecciosa relacionada a fatores sociais e econômicos, ainda muito presente no Brasil. Objetivo: O presente estudo teve como objetivo traçar o perfil epidemiológico da Hanseníase no Brasil, no período de 2016 e 2020. Métodos: Trata-se de um estudo epidemiológico descritivo, retrospectivo com abordagem quantitativa. Os dados foram obtidos por meio da consulta ao Departamento de Informática do Sistema Único de Saúde (DATASUS). Resultados: A Hanseníase ainda é um prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…In this investigation, the predominant operational classification of leprosy was multibacillary (2,663 cases), corroborating studies that point to multibacillary forms as the main responsible for disease transmission [16][17][18].…”
Section: Discussionsupporting
confidence: 88%
“…In this investigation, the predominant operational classification of leprosy was multibacillary (2,663 cases), corroborating studies that point to multibacillary forms as the main responsible for disease transmission [16][17][18].…”
Section: Discussionsupporting
confidence: 88%
“…Analyzing the distribution of cases by age group, it was observed that the majority of patients (94%) were aged 15 or over, with only 6% under 14 years of age. According to Brito Moreira et al [ 35 ], leprosy is considered a disease affecting adults and young adults, and due to its evolution with a high degree of physical disability, it can cause significant social harm to patients, especially those in economically active age groups, while also affecting their mental health due to the associated social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Aquim et al(2020) apontam todos esses ganhos funcionais supracitados em concordância com os outros autores, porém, em relação ao tempo de permanência na UTI, a MP não interfere de forma significativa, mas auxilia na diminuição do tempo de duração da VM. Em consonância com os demais autores,Moreira et al (2020) enfatizam também que a MP gera impacto positivo nas repercussões hemodinâmicas e respiratórias, mas não há diferenças significativas no tempo de internamento hospitalar. Em uma UTI é habitual que os pacientes perdurem restritos ao leito.…”
unclassified